Dyslipidemia in diffuse large B-cell lymphoma based on the genetic subtypes: a single-center study of 259 Chinese patients - Xu, Yi; Shen, Huafei; Shi, Yuanfei; Zhao, Yanchun; Zhen, Xiaolong; Sun, Jianai; Li, Xueying; Zhou, De; Yang, Chunmei; Wang, Jinhan; Huang, Xianbo; Wei, Juying; et al. (Frontiers in Oncology, 2023)
Background Diffuse large B-cell lymphoma (DLBCL) is a kind of highly heterogeneous non-Hodgkin lymphoma, both in clinical and genetic terms. DLBCL is admittedly categorized into six subtypes by genetics, which contain MCD, BN2, EZB, N1, ST2, and A53. Dyslipidemia is relevant to a multitude of solid tumors and has recently been reported to be associated with hematologic malignancies. We aim to present a retrospective study investigating dyslipidemia in DLBCL based on the molecular subtypes. Results This study concluded that 259 patients with newly diagnosed DLBCL and their biopsy specimens were available for molecular typing. Results show that the incidence of dyslipidemia (87.0%, p <0.001) is higher in the EZB subtype than in others, especially hypertriglyceridemia (78.3%, p = 0.001) in the EZB subtype. Based on the pathological gene-sequencing, patients with BCL2 gene fusion mutation are significantly correlative with hyperlipidemia (76.5%, p = 0.006) and hypertriglyceridemia (88.2%, p = 0.002). Nevertheless, the occurrence of dyslipidemia has no remarkable influence on prognosis. Conclusion In summary, dyslipidemia correlates with genetic heterogeneity in DLBCL without having a significant influence on survival. This research first connects lipids and genetic subtypes in DLBCL.